Quantitative evaluation of palatal bone thickness in patients with normal and open vertical skeletal configurations using cone-beam computed tomography - Piyoros Suteerapongpun (2018)
© 2018 by Korean Academy of Oral and Maxillofacial Radiology. Purpose: To perform a comparative analysis of the palatal bone thickness in Thai patients exhibiting class I malocclusion according to whether they exhibited a normal or open vertical skeletal configuration using cone-beam computed tomography (CBCT). Materials and Methods: Thirty CBCT images of Thai orthodontic patients (15-30 years of age) exhibiting class I malocclusion with a normal or open vertical skeletal configuration were selected. Palatal bone thickness was measured in a 3.0-mm grid pattern on both the right and left sides. The palatal bone thickness of the normal-bite and open-bite groups was compared using the independent t-test. The level of significance was established at P < .05. Results: The palatal bone thickness in the normal-bite group ranged from 2.2±1.0 mm to 12.6±4.1 mm. The palatal bone thickness in the open-bite group ranged from 1.9±1.1 mm to 13.2±2.3 mm. The palatal bone thickness was lower at almost all sites in patients with open bite than in those with normal bite. Significant differences were found at almost all anteroposterior sites along the 3 most medial sections (3.0, 6.0, and 9.0 mm lateral to the midsagittal plane) (P < .05). Conclusion: Class I malocclusion with open vertical skeletal configuration may affect palatal bone thickness, so the placement of temporary anchorage devices or miniscrew implants in the palatal area in such patients should be performed with caution.